Empirical analysis on the impact of financial technology at the financial system towards the performance of financial institutions in Malaysia - Liew Li Ling; Caroline Geetha (Penerbit Universiti Malaysia Sabah, 2025)
This research aimed to identify the impact of financial technology in the financial system towards the performance of financial institutions in Malaysia, in the short run and long run. The performance of financial institutions which refers to the profitability of the financial institution after the utilization of financial technology into the daily transactions. A framework which included return on equity (ROE) as a dependent variable, fintech application, size of financial institutions, age of financial institutions as independent variables while Gross Domestic Product (GDP) and inflation act as controlled variables was designed. Quantitative methods which involved secondary data from eight local banks financial reports that range from 2004 to 2023 were analyzed using the panel data analysis with the help of software like Stata and MS Excel. The highlight of this study is the financial technology application which was represented by the digital innovation index. The analysis begins with unit root test, then followed by diagnostic tests such as autocorrelation, normality, stability, multicollinearity, heteroskedasticity tests will be conducted to ensure the validity and the reliability of the model. The findings revealed that mobile banking, earnings per share, size and GDP had a significantly positive relationship with the institution's performance. All other factors were found to be insignificant.